2013
DOI: 10.1002/bjs.8957
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for major morbidity after liver resection for hepatocellular carcinoma

Abstract: Repeat hepatectomy and prolonged surgery were identified as risk factors for bile leakage after liver resection for HCC. Bile leakage and repeat hepatectomy increased the risk of organ/space SSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 30 publications
5
65
2
Order By: Relevance
“…Consistent with the findings of the present study, several reports have indicated that postoperative bile leakage and repeat resection are independent risk factors for postoperative organ/space SSI [2,17]. Indeed, bile leakage has been considered the main cause of morbidity after hepatectomy because bile juice in the dead space predisposes to infection [23].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Consistent with the findings of the present study, several reports have indicated that postoperative bile leakage and repeat resection are independent risk factors for postoperative organ/space SSI [2,17]. Indeed, bile leakage has been considered the main cause of morbidity after hepatectomy because bile juice in the dead space predisposes to infection [23].…”
Section: Discussionsupporting
confidence: 80%
“…Categorical variables are presented as number (%) and were analyzed using the χ 2 Fisher exact test as appropriate. A multivariate analysis was performed by logistic regression and the backward elimination procedure, using p values <0.10 as the cutoff value for elimination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Re‐hepatectomy is thought to be useful for improving long‐term survival in recurrent HCC and L‐Mets;104, 105, 106 however, such procedures can be technically challenging because of conditions created by the first surgery 107. As mentioned earlier, when performed as the first surgery, LLR is associated with minor, or no, adhesion in the abdominal cavity, except at resection margins in the liver.…”
Section: Indications and Oncological Outcomesmentioning
confidence: 99%